Transduction of chemical into electrical energy. - Nachmansohn, D (1976)
The paper recalls some fundamental notions, developed by Otto Meyerhof, which were used in the analysis of the transduction of chemical into mechanical energy during muscular contraction. These notions formed the basis of the approach to the analysis of the transduction of chemical into electrical energy, i.e., the very principle underlying nerve and muscle excitability and bioelectricity. Instrumental for this purpose was the use, since 1937, of electric organs of fish, a tissue highly specialized for bioelectrogenesis.